Thermodynamic and XRD analysis of reaction behaviors of gangue minerals in roasting mixture of scheelite and calcium carbonate for Ca3WO6 preparation. (November 2016) - Li, Xiaobin; Xu, Xiangming; Zhou, Qiusheng; Qi, Tiangui; Liu, Guihua; Peng, Zhihong; Cui, Yuanfa; Li, Jianpu
Abstract: The conversion of unleachable scheelite (CaWO4 ) to readily soluble Ca3 WO6 in aqueous ammonium carbonate solution by roasting is crucial to the development of a green manufacturing technique for ammonium paratungstate. To better understand the influences of gangue minerals on the conversion of CaWO4 to Ca3 WO6, the reaction behaviors of gangue minerals in the scheelite concentrate such as quartz (SiO2 ), apatite (Ca5 (PO4 )3 F), cassiterite (SnO2 ), pyrite (FeS2 ), molybdenite (MoS2 ), and arsenopyrite (FeAsS) in the roasting process were investigated systematically in this work. Thermodynamic analyses and experimental results show that the gangue minerals except Ca5 (PO4 )3 F can react with CaCO3 or Ca3 WO6 to form corresponding calcium-containing compounds in roasting. There are Ca3 Fe2 WO9, CaMoO4, CaSO4, and Ca3 (AsO4 )2, etc. observed in the products when roasting in an oxidizing atmosphere, and Ca2 FeWO6, CaS in a neutral or weakly reducing atmosphere, while the formations of Ca2 SiO4, Ca4 Si2 O7 F2, Ca5 (PO4 )3 F, CaSnO3, and Ca2 SnO4, etc. are independent of roasting atmosphere. The results suggest that these gangue minerals consume calcium and thus affect the conversion of CaWO4 to Ca3 WO6 in the roasting process, which can help determine the appropriate composition dosage for the complete conversion of CaWO4 to Ca3 WO6 . Highlights: Gangue minerals except Ca5 (PO4 )3 F can react with CaCO3 or Ca3 WO6 in roasting. Ca3 Fe2 WO9 and CaSO4 are generated in oxidizing roasting, while Ca2 FeWO6 and CaS in neutral or weakly reducing roasting. The formations of Ca2 SiO4, Ca4 Si2 O7 F2, Ca5 (PO4 )3 F, CaSnO3, and Ca2 SnO4 are independent of roasting atmosphere. Arsenic is retained in roasted product as Ca3 (AsO4 )2 in oxidizing roasting, or volatilized in neutral or weakly reducing roasting.